TINJAUAN HUKUM TERHADAP PENERAPAN ASAS-ASAS DALAM UNDANG-UNDANG PERKAWINAN DI INDONESIA - Sulasno Sulasno; Fitria Agustin Fitria Agustin (LPPM STIA Banten, 2018)
Law Number 1 Year 1974 on Marriage is a Law that regulates how the marriage moment is implemented in Indonesia. In this Law there are several principles that become the foundation in the implementation of Marriage in Indonesia. That marriage is an innerborn bond to form a family, that marriage is lawful if exercised according to religion and belief, that the moment of marriage must be recorded, that marital status in marriage is equal, that there is an age limit in marriage, that the principle of Indonesian marriage adheres to the principle of monogamy , that complicated perceraain is part of the principles in Marriage. This research is aimed to get answers to the problem: How is the Application of Principles in Marriage Law in Indonesia? The invention of the answer to this question is pursued by the Empirical Normative Legal Research Method. The law acts as a Norm (Legislation), with due regard to social reality. The results of the study are: That for the sake of the implementation of the purpose of marriage, the principle in the Law of Marriage must be implemented. That there should be freedom without coercion in marriage, that a husband and wife should be a religionist, that there are sanctions for officials who do not register marriage, that men may only have one wife as women may only have one husband. That the reasons for divorce and its implementation should be carried out before the Court. Thus if these principles are implemented there will be a purpose of marriage. The state must provide space and facilities so that these principles can be established. As a basis that the obligation of the State is to be a forum for the implementation of religious activities carried out.